(untitled) (Rehabilitation and Recreation, 2024)
Periodontal disease represents a crucial interdisciplinary medical challenge. Pathological alterations in periodontal tissues result from the intricate interplay of endogenous and exogenous factors. Among the epidemiological, social, and climatic predictors of the deterioration of the health of the working population, technological factors hold a prominent position. Medicine’s pivotal objective involves devising and implementing methods that enhance the functional state of organs and systems while activating the body’s defense mechanisms. Ozone therapy is a highly effective non-medicinal treatment method, leveraging medical ozone for both general and local impacts on the human body. While not a pharmacological drug, ozone exhibits heightened sensitivity to staphylococci, streptococci, and enterococci, rendering it a potent and safe antibacterial agent in dentistry. Our study aimed to assess the effectiveness of a comprehensive treatment approach for generalized periodontitis, incorporating ozone therapy, among workers exposed to harmful factors in industrial enterprises. This evaluation relied on immunological indicators obtained from oral fluid analysis. The comprehensive treatment of initial II degree and I generalized periodontitis involved 50 employees from three industrial enterprises in the Ivano-Frankivsk region: chemical production, glass production, and the agro-industrial complex, aged 25–55. Participants were segregated into two treatment groups: the main group – 25 individuals receiving the devised treatment and prevention regimen, including ozone therapy; and a control group of 25 patients treated for generalized periodontitis using conventional methods. To gauge the efficacy of treatment and prevention protocols, the dynamics of immunological indicators of oral fluid: secretory sIgA, IgA and the inflammatory marker IgM were observed in both treatment groups 1 and 6 months after treatment of generalized periodontitis. The application of the developed algorithm for the treatment of generalized periodontitis in workers of industrial enterprises, which were part of the main group, had a positive effect on immunological indicators both in the near and in the distant periods of observation. In the control group, the positive dynamics of the immunogram was observed only 1 month after the treatment of periodontal pathology, however, after six months, the determined immunological indicators approached or exceeded the initial data, which proved the insufficient effectiveness of the traditional treatment and prevention scheme. Thus, the treatment and prevention algorithm developed and put into practice made it possible to significantly increase the effectiveness of treatment of generalized periodontitis in workers of industrial enterprises with harmful factors, which was confirmed by a reliable improvement of the local immunity of the oral cavity.